Hidden aftershocks of the 2011 Mw 9.0 Tohoku, Japan earthquake imaged with the backprojection method. Issue 10 (29th October 2013) - Kiser, Eric; Ishii, Miaki
Abstract [1] The first 25 h of the aftershock sequence following the 11 March 2011 Mw 9.0 Tohoku, Japan earthquake is investigated using a backprojection method. In total, 600 aftershocks are imaged during this time period. These aftershocks are distributed over a 500 by 300 km area and include many events in the outer rise. The backprojection events are compared with the Japan Meteorological Agency (JMA) catalogue, which is composed of earthquakes recorded by local seismic networks in Japan. Surprisingly, half of the backprojection events are not found in the JMA catalogue. These events cluster near the Japan Trench and in the outer rise and fill in gaps in the spatial distribution of the early aftershock sequence where large main shock slip is thought to have occurred. These results show that the JMA magnitude of completeness is very high near the trench following the 2011 Tohoku main shock, and earthquakes as large as magnitude 6.8 went undetected by local seismic networks.